Relationship between Psychosocial Risk Factors and Work-Related Musculoskeletal Disorders among Public Hospital Nurses in Malaysia - Amin, Nur Azma (Ann Occup Environ Med, 2014)
OBJECTIVE: This study examined the relationships between psychosocial work factors and risk of WRMSDs among public hospital nurses in the Klang Valley, Malaysia. METHODS: We conducted a cross-sectional study among 660 public hospital nurses. A self-administered questionnaire was used to collect data on the occurrence of WRMSDs according to body regions, socio-demographic profiles, occupational information and psychosocial risk factors. 468 questionnaires were returned (response rate of 71%), and 376 questionnaires qualified for subsequent analysis. Univariate analyses were applied to test for mean and categorical differences across the WRMSDs; multiple logistic regression was applied to predict WRMSDs based on the Job Strain Model’s psychosocial risk factors. RESULTS: Over two thirds of the sample of nurses experienced discomfort or pain in at least one site of the musculoskeletal system within the last year. The neck was the most prevalent site (48.94%), followed by the feet (47.20%), the upper back (40.69%) and the lower back (35.28%). More than 50% of the nurses complained of having discomfort in region one (neck, shoulders and upperback) and region four (hips, knees, ankles, and feet). The results also revealed that psychological job demands, job strain and iso-strain ratio demonstrated statistically significant mean differences (p < 0.05) between nurses with and without WRMSDs. According to univariate logistic regression, all psychosocial risk factors illustrated significant association with the occurrence of WRMSDs in various regions of the body (OR: 1.52–2.14). Multiple logistic regression showed all psychosocial risk factors were significantly associated with WRMSDs across body regions (OR: 1.03–1.19) except for region 1 (neck, shoulders and upper back) and region 4 (hips, knees, ankles, and feet). All demographic variables except for years of employment were statistically and significantly associated with WRMSDs (p < 0.05). CONCLUSIONS: The findings indicated the high prevalence of WRMSDs in many body regions, and the risks of developing WRMSDs according to the various body regions were associated with important psychosocial risk factors based on the job strain model. These findings have implications for the management of WRMSDs among public hospital nurses in the Klang Valley, Malaysia.